ANALISIS PERENCANAAN PEMETAAN KAWASAN DAN PENERAPAN KEPEMILIKAN IJIN PENAMBANGAN PASIR YANG BERLEBIHAN DAN ILEGAL - Lisda Situmorang, Emmy; Revida, Erika; Hasiholan Hutagalung, Mulatua (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
The purpose of this study was to determine the planning of areas and the implementation of excessive and illegal sand mining permit ownership. This type of research is qualitative. Primary and secondary data were used as the data sources. The primary data were based on interview results. Secondary data uses figures and data, books and scientific journals which are used as the basis for scientific literature. The data analysis technique uses thematic analysis. Primary data are obtained from interviews with the Environmental Service and Mining Actors or workers in the Humbang Hasundutan Regency. The results of the study showed that sand mining in Purba Baringin Village, Pakkat District, and Humbang Hasundutan Regency was still found in many who did not have permits, and many met the need for sand from outside the district itself.